Pengaruh Pemanfaatan Riau Pos Sebagai Media Komunikasi Politik Calon Gubernur Riau Abdul Wahid pada Pemilihan Gubernur Riau Tahun 2024 - M. Fajarul Amrie; Yantos Yantos (Yayasan Almanar Pujud, 2025)
This research aims to determine how Riau Pos is utilized as a medium of political communication by Riau Governor candidate Abdul Wahid in the 2024 Riau gubernatorial election. The study employs a qualitative descriptive approach using Harold D. Lasswell's Communication Model, which consists of five components: Who, Says What, In Which Channel, To Whom, and With What Effect. Data were collected through in-depth interviews with three groups of informants: Abdul Wahid’s campaign team (political communicator), Riau Pos journalists (media), and Riau Pos readers (audience). The results indicate that Riau Pos plays a significant and beneficial role as a political communication medium for Abdul Wahid. His campaign team used Riau Pos as the main channel to deliver political messages. Riau Pos was chosen due to its high credibility, wide readership, and strong influence in shaping public opinion in Riau Province. The effectiveness of political communication through Riau Pos is reflected in three aspects: (1) increased public knowledge of Abdul Wahid’s programs (cognitive effect), (2) the emergence of sympathy and trust toward the candidate (affective effect), and (3) influence on voter behavior (conative effect). Thus, it can be concluded that Riau Pos is highly beneficial and plays a strategic role as Abdul Wahid’s political communication medium in the 2024 Riau gubernatorial election.